Desperate remedies : psychiatry's turbulent quest to cure mental illness - Scull, Andrew, 1947- (The Belknap Press of Harvard University Press, 2022)
"A sweeping history of American psychiatry-from jails to hospitals to the lab to the analyst's couch-by the award-winning author of Madness in Civilization. For more than two hundred years, disturbances of the mind-the sorts of things that were once called "madness"-have been studied and treated by the medical profession. Mental illness, some insist, is a disease like any other, whose origins can be identified and from which one can be cured. But is this true? In this masterful account of America's quest to understand and treat everything from anxiety to psychosis, one of the most provocative thinkers writing about psychiatry today sheds light on its tumultuous past. Desperate Remedies brings together a galaxy of mind doctors working in and out of institutional settings: physicians and psychoanalysts, psychologists, neuroscientists, and therapists, social reformers and advocates of mental hygiene, as well as patients and their families desperate for relief. Andrew Scull begins with the birth of the asylum in the reformist zeal of the 1830s and carries us through to the latest drug trials and genetic studies. He carefully reconstructs the rise and fall of state-run mental hospitals, showing how the mentally ill went from prisons to asylums back to prisons, and explaining why so many of the mentally ill are now on the street. In his compelling closing chapters, he reveals how drug companies expanded their reach to treat a growing catalog of ills, deliberately concealing debilitating side effects. Deeply researched and compulsively readable, Desperate Remedies is a definitive account of America's long battle with mental illness that challenges us to rethink our deepest assumptions about who we are and how we think"--